2003
DOI: 10.1364/oe.11.001385
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton plasmon-resonance microscopy

Abstract: A novel method for detection of noble-metal nanoparticles by their nonlinear optical properties is presented and applied for specific labeling of cellular organelles. When illuminated by laser light in resonance with their plasmon frequency these nanoparticles generate an enhanced multiphoton signal. This enhanced signal is measured to obtain a depth-resolved image in a laser scanning microscope setup. Plasmon-resonance images of both live and fixed cells, showing specific labeling of cellular organelles and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
155
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(156 citation statements)
references
References 24 publications
(31 reference statements)
1
155
0
Order By: Relevance
“…It is worth noting that in addition to their enhanced TPL, the gold nanorods can provide orientational information as recently demonstrated by Sönnichsen and Alivisatos (28). The gold nanorods are also essentially inert to photobleaching, a quality whose practical consequences are widely appreciated in biophotonic applications (17,28). TPL Autocorrelation Measurements.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is worth noting that in addition to their enhanced TPL, the gold nanorods can provide orientational information as recently demonstrated by Sönnichsen and Alivisatos (28). The gold nanorods are also essentially inert to photobleaching, a quality whose practical consequences are widely appreciated in biophotonic applications (17,28). TPL Autocorrelation Measurements.…”
Section: Resultsmentioning
confidence: 91%
“…For example, Mohamed et al (11) have observed that the quantum efficiency of singlephoton luminescence from gold nanorods is enhanced by a factor of Ͼ1 million under plasmon-resonant conditions. Plasmonresonant TPL is attractive for nonlinear optical imaging of biological samples with 3D spatial resolution (17). Gold nanorods are particularly appealing as TPL substrates because their longitudinal plasmon modes are resonant at near-infrared, where the absorption of water and biological molecules are minimized.…”
mentioning
confidence: 99%
“…4 In addition, the high biocompatibility of gold nanoparticles has stimulated their widespread use in the biosciences within the last few years. [5][6][7][8][9][10] Gold particles were used as intramolecular distance rulers, 5 as non bleaching sensors, 6 and as labels for multiphoton microscopy. 10 Simultaneously, novel optical microscopic techniques were developed in order to detect and characterize single nanoparticles.…”
mentioning
confidence: 99%
“…Cellular uptake of gold nanorods was visualized by two-photon luminescence microscope. 45,46) To detect two-photon luminescence, femtosecond pulsed laser light is required to observe the uptake; however, it can be expanded to direct imaging of single gold nanorods in vivo. 47) Photoacoustic imaging is a well-known imaging technique for non-invasive imaging of deep tissues, in which gold nanorods act as contrast agent.…”
Section: Fig 3 Normalized Absorption Spectra Of Gold Nanorods Havinmentioning
confidence: 99%